Structure of Coagulation Factor II: Molecular Mechanism of Thrombin Generation and Development of Next-Generation Anticoagulants - Chinnaraj, Mathivanan; Planer, William; Pozzi, Nicola (Frontiers in Medicine, 2018)
Coagulation factor II, or prothrombin, is a multi-domain glycoprotein that is essential for life and a key target of anticoagulant therapy. In plasma, prothrombin circulates in two forms at equilibrium, “closed” (∼80%) and “open” (∼20%), brokered by the flexibility of the linker regions. Its structure remained elusive until recently when our laboratory solved the first X-ray crystal structure of the zymogen locked in the predominant closed form. Because of this technical breakthrough, fascinating aspects of the biology of prothrombin have started to become apparent, and with this, novel and important questions arise. Here, we examine the significance of the “closed”/“open” equilibrium in the context of the mechanism of thrombin generation. Further, we discuss the potential translational opportunities for the development of next-generation anticoagulants that arise from this discovery. By providing a structural overview of each alternative conformation, this minireview also offers a relevant example of modern structural biology and establishes a practical workflow to elucidate the structural features of analogous clotting and complement factors. ​